Analysis of Iran's Maritime Strategy in the Strait of Hormuz Under Admiral Tangsiri's Leadership - Zahra, Raesha Syahnaz; Ruslinar, Meli; Faisal, Muhamad; Triyani, Triyani; Oktaviandra, Yosyea; Novitasari, Yussie; Prakoso, Lukman Yudho; Suwarno, Panji (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Iran has long utilized the Strait of Hormuz as a strategic tool to strengthen its position in regional and global geopolitics. The research method is qualitative descriptive. Data analysis uses SWOT to evaluate the strengths, weaknesses, opportunities, and threats in the maritime strategy in the Strait of Hormuz. The research results show that Iran's maritime strategy under Admiral Tangsiri has evolved by enhancing asymmetric defense capabilities, utilizing fast boats, drones, and anti-ship missiles to threaten ships passing through the strait. The analysis includes geopolitical, economic, and security factors influencing maritime policy, as well as how the strategy is used as a tool of diplomacy and military power. Iran has successfully projected its maritime power in the Strait of Hormuz as a form of strategic defense against external threats, despite facing challenges from complex regional dynamics.